Pengaruh Penambahan Ekstrak Jahe (Zingiber officinale) dalam Proses Pengasinan terhadap Karakteristik Organoleptik Telur Asin - Icha Tridayana; Sonya Elisabeth Silaen; Nailis Salsabila; Tsamara Nur Rahmah; Zahra Radliyatam Mardliyah (Social Science Academic, 2026)
The addition of natural ingredients during the salting process is one approach to improving the sensory quality and consumer acceptance of salted eggs. Ginger (Zingiber officinale) contains bioactive compounds and flavor components that have the potential to enhance the organoleptic characteristics of food products. This study aimed to evaluate the effect of ginger extract addition during the salting process on the organoleptic characteristics of salted eggs. A Completely Randomized Design (CRD) was employed with five treatments: P0 (0 g ginger extract/L water), P1 (150 g ginger extract/L water), P2 (200 g ginger extract/L water), P3 (250 g ginger extract/L water), and P4 (300 g ginger extract/L water), each with three replications. Organoleptic evaluation was conducted by 100 untrained panelists on ginger aroma, egg white texture, egg yolk texture, ginger taste, and fishy taste of salted eggs. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test. The results showed that the addition of ginger extract had no significant effect (P>0.05) on ginger aroma, but significantly affected egg white texture (P<0.01), egg yolk texture (P<0.05), ginger taste (P<0.05), and fishy taste (P<0.05). Treatment P4 produced the highest scores for egg white texture, ginger taste, and fishy taste, while the highest egg yolk texture score was observed in treatment P2. The addition of ginger extract improved the organoleptic quality of salted eggs by enhancing texture, increasing ginger flavor intensity, and reducing the perception of fishy taste. It can be concluded that ginger extract has potential as a natural additive in the salting process to improve the sensory quality of salted eggs.